Motivation and self-regulation as predictors of e-learning experience among undergraduates in a Malaysian Public University - Chiang, Yan Chiou (2015)
This study was carried out to identify the relationship between motivation and selfregulation towards e-learning experiences among undergraduates at Universiti Putra Malaysia (UPM). For this purpose, a total of 314 samples were selected from undergraduates in UPM. Data were collected using a questionnaire and analysed using Statistical Package for Social Sciences (SPSS) version 20. A descriptive analysis was completed to obtain both mean and standard deviation of the variables. Findings from the descriptive analysis showed that students are motivated and self-regulated when using PutraLMS. Besides, students also had positive perception or were satisfied with PutraLMS. Meanwhile, inferential analysis showed a significant positive relationship between motivation (r = 0.589, p = 0.0001) and self-regulation (r = 0.632, p = 0.0001) towards e-learning experiences. In addition, multiple linear regression analysis was also used to identify predictive factors of two independent variables that influence e-learning experience. Results showed that self-regulation (β = 0.421, p = 0.0001) was a better predictor for e-learning experience as compared to motivation (β = 0.413, p = 0.0001). The results revealed that the final two predictors model explained about 54.2% of the variation in e-learning experiences. This finding suggests that students generally view PutraLMS as an useful tool that supports them in their face-to-face classes. With an elearning environment that supports students’ motivation and self-regulation, students are likely to have a positive perception and feel satisfied to using PutraLMS. Finally,PutraLMS has been certified as a suitable tool to assist face-to-face classes in UPM,where students are satisfied with the PutraLMS environment, as shown in this study.